2023
DOI: 10.3390/su15043835
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management and Reverse Logistics on Recycling in a War Scenario

Abstract: Nowadays organizations search to maximize their profits, particularly with regard to recyclable materials, making new strategies according to several emerging and changing scenarios. Logistics management is an important tool in achieving these goals, serving as a link between the market and the various areas of an organization. It is responsible for managing physical and organizational flows, both within and between organizations. Reverse logistics management of waste is one of the most complex areas in any or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%
“…This complicates the management of logistics for the materiel supply. Existing publications consider the materiel supply in peacetime for the formation of the planned reserves in case of war, and not during military operations [11][12][13].…”
Section: State Of the Artmentioning
confidence: 99%
“…Challenges and threats lead to an increase in risks (political-economic, climatic, terroristic and military threats, etc.) [10,11]. In conditions of a stable economy, long logistics chains are economically profitable due to small threats [12,13].…”
Section: State Of the Artmentioning
confidence: 99%